A photocured alumina ceramic slurry, preparation method and application thereof
By using photocured alumina ceramic slurry, combined with the ratio of nano alumina powder and specific photosensitive resin, the problems of low accuracy, poor integrity and insufficient moldability in 3D printed alumina ceramic technology are solved, and 3D printing effect with high precision and excellent molding is achieved.
Patent Information
- Application Number
- CN202411259673.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing 3D printing alumina ceramic technology has problems such as low printing accuracy, poor product integrity and insufficient moldability.
Photocured alumina ceramic slurry is used, which consists of nano-alumina powder, photosensitive resin, photoinitiator, dispersant and free radical polymerization inhibitor, and is prepared through specific ratios and mixing methods to achieve 3D printing of micro-nano-level accuracy.
It achieves high precision, good integrity and excellent molding effect of 3D printing products, significantly improving printing accuracy and molding quality.
Smart Images

Figure CN118771862B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of 3D printing, and in particular relates to a photocured alumina ceramic slurry, a preparation method and application thereof. Background Art
[0002] Alumina ceramics are widely used in electronic ceramics, functional ceramics and structural ceramics due to their excellent physical and chemical properties such as high melting point, high boiling point, high hardness, wear resistance, and good electrical properties. Traditional alumina ceramic forming methods such as dry pressing, slip casting, and tape casting have the problem of low precision in special-shaped structures; although the computer numerical control (CNC) forming method can achieve a high level of precision, due to the brittleness of alumina ceramics, defects are easily generated through CNC forming, and the ultimate precision is insufficient. It can be seen that the printing precision of ordinary 3D printed alumina ceramics is generally low.
[0003] Therefore, there is an urgent need to develop a photocurable alumina ceramic slurry that has high printing precision, good printing product integrity, and good printing product formability during the 3D printing process. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a photocured alumina ceramic slurry and a preparation method thereof. The photocured alumina ceramic slurry of the present invention can realize 3D printing with micro-nano level precision, and the printed product has good integrity and formability.
[0005] Specifically, the present invention provides a photocurable alumina ceramic slurry, which comprises nano alumina powder, a photosensitive resin, a photoinitiator, a dispersant and a free radical inhibitor; in the photocurable alumina ceramic slurry, the mass fraction of the nano alumina powder is 70% to 82%, the mass fraction of the photosensitive resin is 10% to 28%, the mass fraction of the photoinitiator is 0.5% to 3%, the mass fraction of the dispersant is 1% to 5%, and the mass fraction of the free radical inhibitor is 0.15% to 0.25%; the photosensitive resin is a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and trimethylolpropane triacrylate in a mass ratio of 1:(0.8-1.2):(1.2-1.5).
[0006] In one or more embodiments, the particle size D50 of the nano-alumina powder is 100-1000 nm.
[0007] In one or more embodiments, the photoinitiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and 1-hydroxycyclohexylphenyl ketone.
[0008] In one or more embodiments, the dispersant is selected from one or more of BYK-102, BYK-180, BYK-9076, BYK-109, BYK-108, and BYK-110.
[0009] In one or more embodiments, the free radical inhibitor is selected from one or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, 4,4′-dihydroxybiphenyl and bisphenol A.
[0010] The present invention provides a method for preparing the light-cured alumina ceramic slurry of the present invention, the method comprising the following steps:
[0011] (1) Mix the photosensitive resin, photoinitiator and free radical inhibitor evenly;
[0012] (2) Adding nano-alumina powder and a dispersant to the mixture obtained in step (1), mixing them evenly and filtering them to obtain a light-cured alumina ceramic slurry.
[0013] In one or more embodiments, in step (1), the mixing is performed under vacuum conditions.
[0014] In one or more embodiments, in step (2), the mixing is performed under vacuum conditions.
[0015] The present invention provides an application of a light-cured alumina ceramic slurry in 3D printing.
[0016] The present invention provides an alumina ceramic material or product, wherein the alumina ceramic material or product is prepared by 3D printing using the light-cured alumina ceramic slurry described in the present invention.
[0017] Compared with the prior art, the present invention has the following beneficial effects: the products printed by the photocured alumina ceramic slurry of the present invention in 3D printing have high precision, good integrity of the printed products, and good molding effect of the printed products. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Example 1 of the present invention.
[0019] Figure 2 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Example 2 of the present invention.
[0020] Figure 3 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 1 of the present invention.
[0021] Figure 4 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 2 of the present invention.
[0022] Figure 5 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 3 of the present invention.
[0023] Figure 6 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 4 of the present invention.
[0024] Figure 7 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 5 of the present invention.
[0025] Figure 8 This is a local high-magnification microscope magnified image of the honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 5 of the present invention.
[0026] Fig. 9 This is a microscope magnified image of the small hole sample printed by the 3D photocured alumina ceramic slurry prepared in Example 2 of the present invention.
[0027] Fig.10 This is a magnified microscope image of a honeycomb sample printed with 3D photocured alumina ceramic slurry prepared in Comparative Example 6 of the present invention. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.
[0029] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0030] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0031] In this document, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0032] Herein, the sum of the percentages of the various components in the composition is 100%.
[0033] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0034] Herein, when describing embodiments or examples, it should be understood that it is not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined herein.
[0035] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0036] The present invention provides a photocurable alumina ceramic slurry, which may include nano alumina powder, photosensitive resin, photoinitiator, dispersant and free radical inhibitor. The photocurable alumina ceramic slurry of the present invention has suitable viscosity and suitable curing depth. The use of the photocurable alumina ceramic slurry containing the above substances is conducive to obtaining products with high precision, high integrity and good formability in 3D printing.
[0037] In the light-cured alumina ceramic slurry of the present invention, the mass fraction of nano alumina powder is 70% to 82%, for example, 70%, 72%, 74%, 76%, 78%, 80%, and 82%.
[0038] In the photocured alumina ceramic slurry of the present invention, the mass fraction of the photosensitive resin can be 10% to 28%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, and 28%.
[0039] In the photocured alumina ceramic slurry of the present invention, the mass fraction of the photoinitiator can be 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, and 3%.
[0040] In the light-cured alumina ceramic slurry of the present invention, the mass fraction of the dispersant can be 1% to 5%, for example, 1%, 2%, 3%, 4%, or 5%.
[0041] In the photocured alumina ceramic slurry of the present invention, the mass fraction of the free radical inhibitor can be 0.15% to 0.25%, for example, 0.15%, 0.17%, 0.19%, 0.21%, 0.23%, 0.25%. In the present invention, controlling the number of free radical inhibitors within the above range is conducive to obtaining products with high precision and integrity in 3D printing.
[0042] In the present invention, the particle size D50 of the nano-alumina powder can be 100-1000 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm. In the present invention, the particle size D50 of the nano-alumina powder is controlled within the above range, which is conducive to obtaining products with high precision, high integrity and good formability in 3D printing.
[0043] In the present invention, the photosensitive resin may be a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and trimethylolpropane triacrylate preferably in a mass ratio of 1: (0.8-1.2): (1.2-1.5). In the mixture, the mass ratio of 1,6-hexanediol diacrylate and polyethylene glycol diacrylate may be 1: 0.8, 1: 0.85, 1: 0.9, 1: 0.95, 1: 1, 1: 1.05, 1: 1.1, 1: 1.15, 1: 2. In the mixture, the mass ratio of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate may be 1: 1.2, 1: 1.25, 1: 1.3, 1: 1.35, 1: 1.4, 1: 1.45, 1: 1.5. Using the above-mentioned three photosensitive resin mixtures in mass ratio is conducive to obtaining products with high precision, good integrity and good formability in 3D printing. The inventors of the present invention have found that using trimethylolpropane triacrylate as one of the three components of the photosensitive resin is more conducive to obtaining products with high precision, high integrity and good formability in 3D printing, compared with using pentaerythritol triacrylate as one of the three components of the photosensitive resin. This may be because pentaerythritol triacrylate contains hydroxyl groups on its molecular chain, which easily form hydrogen bonds with oxygen atoms in other molecules in the photocurable alumina ceramic slurry, increase the intermolecular force, increase the viscosity of the photocurable alumina ceramic slurry, and thus be unfavorable for the printing and molding of the photocurable alumina ceramic slurry.
[0044] In the present invention, the photoinitiator may be one or more selected from phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide and 1-hydroxycyclohexylphenyl ketone.
[0045] In the present invention, the dispersant may be one or more selected from BYK-102, BYK-180, BYK-9076, BYK-109, BYK-108 and BYK-110.
[0046] In the present invention, the free radical inhibitor may be one or more selected from the group consisting of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, 4,4'-dihydroxybiphenyl and bisphenol A.
[0047] The present invention provides a method for preparing the light-cured alumina ceramic slurry of the present invention, the method comprising the following steps:
[0048] (1) Mix the photosensitive resin, photoinitiator and free radical inhibitor evenly;
[0049] (2) Adding nano-alumina powder and a dispersant to the mixture obtained in step (1), mixing them evenly and filtering them to obtain a light-cured alumina ceramic slurry.
[0050] In step (1), the mixing can be performed under vacuum conditions.
[0051] In step (2), the mixing can be performed under vacuum conditions.
[0052] The photocurable alumina ceramic slurry of the present invention can be used in 3D printing.
[0053] The present invention provides an alumina ceramic material or product, which can be prepared by 3D printing using the light-cured alumina ceramic slurry of the present invention.
[0054] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0055] The nano-alumina powder in the examples and comparative examples of the present invention was purchased from MCC New Materials, and the particle size D50 of the nano-alumina powder was 200 nm.
[0056] The polyethylene glycol diacrylate in the examples and comparative examples of the present invention was purchased from Shanghai Yinchang New Materials Co., Ltd. with a brand number of CAS: 26570-48-9.
[0057] Example 1
[0058] In this embodiment, light-cured alumina ceramic slurry is prepared, and the specific steps are as follows:
[0059] (1) Weigh 20 g of photosensitive resin (the photosensitive resin is a mixture of 30 wt% 1,6-hexanediol diacrylate, 30 wt% polyethylene glycol diacrylate and 40 wt% trimethylolpropane triacrylate), 1.8 g of photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and 0.2 g of free radical inhibitor p-tert-butylcatechol and add them into a plastic jar, place the plastic jar in a homogenizer, mix at 500 rpm under vacuum for 15 min;
[0060] (2) After the first mixing is completed, 75 g of nano-alumina powder and 3 g of dispersant BYK-110 are weighed and added to a plastic tank. The mixture is mixed at 1000 rpm under vacuum conditions for 2 min to ensure that the materials in the plastic tank are fully mixed. After the materials are mixed, the materials in the plastic tank are filtered to obtain a light-cured alumina ceramic slurry.
[0061] Example 2
[0062] The other conditions of this embodiment are the same as those of Embodiment 1, except that the amount of photoinitiator added in this embodiment is 1.5 g, and the amount of dispersant added is 3.3 g.
[0063] Comparative Example 1
[0064] The other conditions of this comparative example are the same as those of Example 1, except that no free radical inhibitor is added in this comparative example, and the added amount of the photosensitive resin is 20.2 g.
[0065] Comparative Example 2
[0066] The other conditions of this comparative example are the same as those of Example 1, except that the amount of the free radical inhibitor added in this comparative example is 0.1 g, and the amount of the photosensitive resin added is 20.1 g.
[0067] Comparative Example 3
[0068] The other conditions of this comparative example are the same as those of Example 1, except that the amount of the free radical inhibitor added in this comparative example is 0.3 g, and the amount of the photosensitive resin added is 19.9 g.
[0069] Comparative Example 4
[0070] The other conditions of this comparative example are the same as those of Example 1, except that the photosensitive resin in this comparative example is a mixture of 30 wt % 4-acryloylmorpholine, 40 wt % 1,6-hexanediol diacrylate and 30 wt % trihydroxymethylpropane triacrylate.
[0071] Comparative Example 5
[0072] The other conditions of this comparative example are the same as those of Example 1, except that the photosensitive resin in this comparative example is a mixture of 40 wt % 1,6-hexanediol diacrylate and 60 wt % ethoxylated trimethylolpropane triacrylate.
[0073] Comparative Example 6
[0074] The other conditions of this comparative example are the same as those of Example 1, except that the photosensitive resin in this comparative example is a mixture of 30 wt % 1,6-hexanediol diacrylate, 30 wt % polyethylene glycol diacrylate and 40 wt % pentaerythritol triacrylate.
[0075] Test Case
[0076] Viscosity test: At 40°C, a digital viscometer was used to test the viscosity of the photocured alumina ceramic slurries prepared in Examples 1-2 and Comparative Examples 1-6 at different rotation speeds. The viscosities of the photocured alumina ceramic slurries prepared in Examples 1-2 and Comparative Examples 1-6 at a rotation speed of 60 rpm were compared. The results are shown in Table 1.
[0077] Curing depth test: at light source power 49831μw / cm 2 Under the conditions of , the photocured alumina ceramic slurries prepared in Examples 1-2 and Comparative Examples 1-6 were scanned for 2s with a 405nm light source to form corresponding cured monolayers. The thickness of the monolayer was tested with a micrometer. The results are shown in Table 1.
[0078] Printing performance test: at light source power 49831μw / cm 2 Under the conditions of , the photocurable alumina ceramic slurries prepared in Examples 1-2 and Comparative Examples 1-6 were scanned with a 405nm light source, the single scanning time was 2s, and a total of 1000 scans were performed to print a 10mm×10mm×10mm alumina ceramic honeycomb sample. The surface quality and integrity of the printed alumina ceramic honeycomb sample can be used to judge the printing performance of the photocurable alumina ceramic slurry; the printed honeycomb sample is as follows Figure 1-Figure 8 and Fig.10 As shown, compared Figure 1-Figure 8 and Fig.10 The integrity and surface quality of the honeycomb samples are shown in Table 1.
[0079] Minimum printable aperture test: at light source power 49831μw / cm 2 Under the condition of , the light-cured alumina ceramic slurry prepared in Example 2 was scanned with a 405nm light source, the single scanning time was 2s, and a total of 200 scans were performed to print a 50μm×50μm×2mm alumina ceramic small hole sample. The minimum printable aperture of the light-cured alumina ceramic slurry can be determined from the small hole size of the printed alumina ceramic small hole sample. The printed small hole sample is as follows Fig. 9 shown.
[0080] Table 1: Viscosity, curing depth and printing performance of the photocured alumina ceramic slurries prepared in Examples 1-2 and Comparative Examples 1-6
[0081]
[0082] Depend on Figure 1 and Figure 2 It can be seen that the samples printed by the light-cured alumina ceramic slurry prepared in Examples 1-2 of the present invention are complete and have no obvious defects on the surface, indicating that the printing performance is good. Figure 3 and Figure 4 It can be seen that the samples printed by the light-cured alumina ceramic slurry prepared in Comparative Examples 1-2 of the present invention are incomplete and have obvious defects on the surface, indicating that their printing performance is poor; Figure 5 It can be seen that the sample printed by the light-cured alumina ceramic slurry prepared in Comparative Example 3 of the present invention cannot be formed; Figure 6 It can be seen that the sample printed by the photocurable alumina ceramic slurry prepared in Comparative Example 4 of the present invention is complete, but there is obvious delamination on the surface, which cannot meet the needs of practical applications. That is, although the photocurable alumina ceramic slurry prepared in Comparative Example 4 can be formed, the forming effect is poor. Figure 7 and Figure 8 It can be seen that the sample printed with the light-cured alumina ceramic slurry prepared in Comparative Example 5 of the present invention only completed a portion of the printing, while the remaining portion failed to complete the printing, that is, the printing could not be completed, and from Figure 8 It can be seen that the surface of the sample is very rough and there is slight delamination.
[0083] Depend on Fig. 9 It can be seen that the minimum printable aperture of the sample printed in Example 2 of the present invention is 50 μm, which indicates that the photocured alumina ceramic slurry of the present invention has high printing accuracy during the 3D printing process.
[0084] Depend on Fig.10It can be seen that when the photosensitive resin is a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and pentaerythritol triacrylate, the layers of the 3D printed product are full of staggered layers and delamination, so the complete model is not printed in the end; further, it can be seen from the viscosity data in Table 1 that under the same conditions, compared with the photosensitive resin in Example 1 prepared from a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and trimethylolpropane triacrylate, the photosensitive resin in Comparative Example 6 is 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and pentaerythritol triacrylate. The photocurable alumina ceramic slurry has a significantly increased viscosity, and the increase in viscosity is not conducive to the printing and molding effect of the photocurable alumina ceramic slurry. In summary, the use of a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and trimethylolpropane triacrylate as a photosensitive resin has an unexpected synergistic effect in achieving 3D printing of products with high precision, high integrity and good formability.
Claims
1. Application of a photocurable alumina ceramic slurry in 3D printing, characterized in that: The photocurable alumina ceramic slurry comprises nano alumina powder, photosensitive resin, photoinitiator, dispersant and free radical inhibitor; In the photocurable alumina ceramic slurry, the mass fraction of the nano alumina powder is 70% to 82%, the mass fraction of the photosensitive resin is 10% to 28%, the mass fraction of the photoinitiator is 0.5% to 3%, the mass fraction of the dispersant is 1% to 5%, and the mass fraction of the free radical inhibitor is 0.15% to 0.25%; The photosensitive resin is a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and trimethylolpropane triacrylate in a mass ratio of 1:(0.8-1.2):(1.2-1.5); The particle size D50 of the nano-alumina powder is 100-1000 nm; The photocured alumina ceramic slurry is prepared by a method comprising the following steps: (1) Mixing the photosensitive resin, photoinitiator and free radical inhibitor uniformly under vacuum conditions; (2) adding nano-alumina powder and a dispersant to the mixture obtained in step (1), mixing them evenly under vacuum conditions, and then filtering to obtain a light-cured alumina ceramic slurry; The light source power of the 3D printing is 49831 μw / cm 2 , the wavelength of the light source is 405nm, and the single scanning time is 2s.
2. The use according to claim 1, characterized in that: The photoinitiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide and 1-hydroxycyclohexylphenyl ketone.
3. The use according to claim 1, characterized in that: The dispersant is selected from one or more of BYK-102, BYK-180, BYK-9076, BYK-109, BYK-108 and BYK-110.
4. The use according to claim 1, characterized in that: The free radical inhibitor is selected from one or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, 4,4'-dihydroxybiphenyl and bisphenol A.
5. An alumina ceramic material or product, characterized in that: The alumina ceramic material or product is prepared by 3D printing using a light-cured alumina ceramic slurry; The photocurable alumina ceramic slurry comprises nano alumina powder, photosensitive resin, photoinitiator, dispersant and free radical inhibitor; In the photocurable alumina ceramic slurry, the mass fraction of the nano alumina powder is 70% to 82%, the mass fraction of the photosensitive resin is 10% to 28%, the mass fraction of the photoinitiator is 0.5% to 3%, the mass fraction of the dispersant is 1% to 5%, and the mass fraction of the free radical inhibitor is 0.15% to 0.25%; The photosensitive resin is a mixture of 1,6-hexanediol diacrylate, polyethylene glycol diacrylate and trimethylolpropane triacrylate in a mass ratio of 1:(0.8-1.2):(1.2-1.5); The particle size D50 of the nano-alumina powder is 100-1000 nm; The photocured alumina ceramic slurry is prepared by a method comprising the following steps: (1) Mixing the photosensitive resin, photoinitiator and free radical inhibitor uniformly under vacuum conditions; (2) adding nano-alumina powder and a dispersant to the mixture obtained in step (1), mixing them evenly under vacuum conditions, and then filtering to obtain a light-cured alumina ceramic slurry; The light source power of the 3D printing is 49831 μw / cm 2 , the wavelength of the light source is 405nm, and the single scanning time is 2s.
6. The alumina ceramic material or product according to claim 5, characterized in that: The photoinitiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide and 1-hydroxycyclohexylphenyl ketone.
7. The alumina ceramic material or product according to claim 5, characterized in that: The dispersant is selected from one or more of BYK-102, BYK-180, BYK-9076, BYK-109, BYK-108 and BYK-110.
8. The alumina ceramic material or product according to claim 5, characterized in that: The free radical inhibitor is selected from one or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, 4,4'-dihydroxybiphenyl and bisphenol A.
Citation Information
Patent Citations
SiC ceramic photosensitive slurry for photocuring 3D printing and preparation method thereof
CN115838288A
3D light-cured zirconia ceramic slurry and preparation method thereof
CN117285348A